Mitochondrial portrait of the Cabo Verde archipelago: the Senegambian outpost of Atlantic slave trade - Brehm, A. (2002)
In order to study the matrilineal genetic composition in Cabo Verde (Republic of Cape Verde), an archipelago that used to serve as a Portuguese entrepôt of the Atlantic slave trade, we have analysed a total of 292 mtDNAs sampled from the seven inhabited islands for the hypervariable segment I (HVS-I) and some characteristic RFLPs of the coding regions. The different settlement history of the northwestern group of the islands is well reflected in the mtDNA pool. The total Cabo Verde sample clearly displays the characteristic mitochondrial features of the Atlantic fringe of western Africa and testifies to almost no mitochondrial input from the Portuguese colonizers.